2019
DOI: 10.1002/slct.201903517
|View full text |Cite
|
Sign up to set email alerts
|

Vertically MoS2 on Reduced Graphene Oxide with Superior Durability for Quasi‐solid‐state Supercapacitor

Abstract: Molybdenum disulfide (MoS2) is a two‐dimensional layer structure with high edge energy state, resulting in high chemical activity. It can be widely used in the supercapacitors. Herein, a novel conductive architectures of MoS2/reduced graphene oxide (rGO) nanosheets was immobilized on carbon cloth (CC) via hydrothermal method. The MoS2/rGO nanosheets are uniformly grown on CC, which can provide a higher specific surface area and increase additional active sites. The intimate contact between nanostructured MoS2/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…For example, metal decoration has been mainly employed to be used as a catalyst 17 . Besides, doping of various carbon materials such as graphene and carbon nanotubes (CNTs) changes the electronic properties, which might be used as an electrocatalyst, sensors, supercapacitors, and electronic devices 18‐23 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, metal decoration has been mainly employed to be used as a catalyst 17 . Besides, doping of various carbon materials such as graphene and carbon nanotubes (CNTs) changes the electronic properties, which might be used as an electrocatalyst, sensors, supercapacitors, and electronic devices 18‐23 …”
Section: Introductionmentioning
confidence: 99%
“…17 Besides, doping of various carbon materials such as graphene and carbon nanotubes (CNTs) changes the electronic properties, which might be used as an electrocatalyst, sensors, supercapacitors, and electronic devices. [18][19][20][21][22][23] Amount difference candidates for preparation of hybrid carbon-based materials, titanium dioxide is a particular candidate for the preparation of photosensitive structures because this metal oxide is known for its promising photocatalytic abilities. [24][25][26] In this line, many research studies have been reported on the preparation and photocatalytic ability of titanium dioxide and its hybrid materials.…”
mentioning
confidence: 99%
“…[7] The transition metal sulfides are more abundant and more stable than their counterpart oxides. Among the transition metal sulfides, the FeS 2 , NiS, ZnS, MoS 2 , [8] and CoS are much famous due to their low cost, [9] higher theoretical capacitance [10] and excellent redox properties. [11] Instead of higher electrochemical potential, pristine TMSs are not suitable for advanced energy storage applications as they offer lower electronic conductivity and limited surface area.…”
Section: Introductionmentioning
confidence: 99%